Palmitoyl transferases act as potential regulators of tumor-infiltrating immune cells and glioma progression - Feng Tang; Chao Yang; Feng-Ping Li; Dong-Hu Yu; Zhi-Yong Pan; Ze-Fen Wang; Zhi-Qiang Li (Elsevier, 2022)
High immune-cell infiltration in glioblastomas (GBMs) leads to immunotherapy resistance. Emerging evidence has shown that zinc finger Asp-His-His-Cyc-type (ZDHHC) palmitoyl transferases participate in regulating tumor progression and the immune microenvironment. In the present study, a large cohort of patients with gliomas from The Cancer Genome Atlas (TCGA) and Rembrandt databases was included to perform omics analysis of ZDHHCs in gliomas. CCK-8, flow cytometry, quantitative real-time PCR, western blotting, and transwell assays were performed to determine the effects of ZDHHC inhibition on glioma cells and microglia. We found that five (ZDHHC11, ZDHHC12, ZDHHC15, ZDHHC22, and ZDHHC23) out of 23 ZDHHCs were aberrantly expressed in gliomas and might play their roles through the phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) signaling pathway. Further results indicated that inhibition of ZDHHCs with 2-bromopalmitate (2-BP) suppressed glioma-cell viability and autophagy, as well as promoted apoptosis. Targeting ZDHHCs also promoted the sensitivity of glioma cells to temozolomide (TMZ) chemotherapy. In addition, the inhibition of ZDHHCs weakened the migratory ability of microglia induced by glioma cells in vitro and in vivo. Taken together, our findings suggest that the inhibition of ZDHHCs suppresses glioma-cell viability and microglial infiltration. Targeting ZDHHCs may be promising for glioma treatments.